PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI SEPEDA MOTOR KAWASAKI - Ahmad Fauzan; Abdul Rohman (STIE Muhammadiyah Jakarta, 2020)
This study aims to determine the effect of prices on buying interest of Kawasaki motorcycles, and the effect of product quality on buying interest of Kawasaki motorbikes at STIE Muhammadiyah Jakarta students. The population in this study were students at STIE Muhammadiyah Jakarta. The sampling technique uses purposive sampling, so that the number of samples is 96 people. Data collection techniques using questionnaires, data analysis techniques used are validity and reliability. Data were analyzed using classic assumption test techniques, multiple linear regression analysis, F test, t test, and coefficient of determination. The results of this study indicate that there is a positive and significant effect between prices on buying interest. This is evidenced by the results of the statistical test of the t test for the price obtained t value of 3.597 with a significant value of 0.001 smaller than 0.05 (0.001 0.05), and the regression coefficient has a positive value of 0.629 and there is a positive influence between quality product towards buying interest. This is evidenced by the results of the t test statistical test for the price obtained t value of 2.054 with a significant value of 0.043 smaller than 0.05 (0.043 0.05), and the regression coefficient has a positive value of 0.339.